Politically connected boards and top executive pay in Chinese listed firms - Chizema, Amon; Liu, Xiaohui; Lu, Jiangyong; Gao, Lan (Strategic Management Journal, 2015)
Drawing on social comparison theory, this study examines the relationship between politically connected boards and top executive pay. Moreover, given the socialist orientation of China, tests are also carried out to establish the relationship between politically connected directors and pay dispersion across the firm. We find a negative association between politically connected boards and top executive pay. We also find that politically connected boards are negatively associated with pay dispersion, i.e., the higher the number of political directors on the board the smaller the gap between top executive pay and average employee pay. Finally, our study shows that politically connected directors weaken the pay‐performance link. These findings have important theoretical, policy, and managerial implications . Copyright © 2014 John Wiley & Sons, Ltd.